INTEGRASI MANAJEMEN STRATEGIS DAN MANAJEMEN KINERJA DALAM PENGEMBANGAN DAYA SAING UMKM - Sodirin Sodirin; Junaidi Junaidi; Hesti Widi Astuti; Pujianto Pujianto (CV. Tripe Konsultan, 2026)
Developing the competitiveness of MSMEs requires an integrated approach between strategic management and performance management so that businesses can survive and grow sustainably. This community service aims to improve the capacity of MSME actors in developing targeted business strategies and implementing a performance management system based on measurable indicators. The implementation methods include needs identification, participatory training, assistance in strategic plan development, Key Performance Indicators (KPI) development, as well as monitoring and evaluation. The results of the activities show an increase in MSME actors' understanding of the importance of business environment analysis, competitive strategy formulation, and periodic business performance measurement. In addition, partner MSMEs have successfully developed simple strategic plans and key performance indicators that can be used as business control tools. The integration of strategic management and performance management has proven to help MSMEs improve operational efficient.